Reconstructing the projected gravitational potential of Abell 1689 from X-ray measurements - Tchernin, Celine; Majer, Charles Ludwig; Meyer, Sven; Sarli-Waizmann, Eleonora; Bartelmann, Matthias (Arxiv, 2015)
Context. Galaxy clusters can be used as cosmological probes, but to this end, they need to be thoroughly understood. Combining all cluster observables in a consistent way will help us to understand their global properties and their internal structure. Aims. We provide proof of the concept that the projected gravitational potential of galaxy clusters can directly be reconstructed from X-ray observations. We also show that this joint analysis can be used to locally test the validity of the equilibrium assumptions in galaxy clusters. Methods. We used a newly developed reconstruction method, based on Richardson-Lucy deprojection, that allows reconstructing projected gravitational potentials of galaxy clusters directly from X-ray observations. We applied this algorithm to the well-studied cluster Abell 1689 and compared the gravitational potential reconstructed from X-ray observables to the potential obtained from gravitational lensing measurements. [...] Results. Assuming spherical symmetry and hydrostatic equilibrium, the potentials recovered from gravitational lensing and from X-ray emission agree very well beyond 500 kpc. Owing to the fact that the Richardson-Lucy deprojection algorithm allows deprojecting each line of sight independently, this result may indicate that non-gravitational effects and/or asphericity are strong in the central regions of the clusters. Conclusions. We demonstrate the robustness of the potential reconstruction method based on the Richardson-Lucy deprojection algorithm and show that gravitational lensing and X-ray emission lead to consistent gravitational potentials. Our results illustrate the power of combining galaxy-cluster observables in a single, non-parametric, joint reconstruction of consistent cluster potentials that can be used to locally constrain the physical state of the gas.